Biting through the Skin : An Indian Kitchen in America's Heartland - Furstenau, Nina (Book collections on Project MUSE., 2013)
At once a traveler's tale, a memoir, and a cookbook, this book offers a first-generation immigrant's perspective on growing up in America's heartland. The author's parents brought her from Bengal in northern India to the small town of Pittsburg, Kansas, in 1964, decades before you could find long-grain rice or plain yogurt in American grocery stores. Embracing American culture, the Mukerjee family ate hamburgers and softserve ice cream, took a visiting guru out on the lake in their motorboat, and joined the Shriners. As a girl and a young woman, the author traveled to her ancestral India, as well as to college and to Peace Corps service in Tunisia. Through her journeys and her marriage to an American man whose grandparents hailed from Germany and Sweden, she learned that her family was not alone in being a small pocket of culture sheltered from the larger world. In mourning the partial loss of her heritage, the author finds that, ultimately, heritage always finds other ways of coming to meet us.